Purification Of Natural Waters - Elza Tursunova (Academia One, 2024)
The safe drinking water has become one of the main components of the overall autonomous water supply, aimed at satisfying the high demands for the quality of the supplied water and full quality in it, should cover not only technical and economic, but also environmental factors. In this article was discussed one of the priority tasks is the preparation of drinking water for domestic and drinking purposes from surface water bodies with a limited flow rate and water quality, formed under the influence of natural and anthropogenic factors. Also, were discussed the methods of pre-treatment of water, both natural and complex multi-stage processes, which can be divided into two stages: mechanical filtration - removal of solid impurities, flakes, fibrous inclusions using a filter and chemical treatment - water passes through sedimentary reservoirs, where methods such as clarification, coagulation, protection, filtration dominate. disinfection, demineralization, softening. The results obtained confirm their role in improving the efficiency of water purification processes, their industrial approbation is presented, improved water purification technologies are considered
Keywords: earth water body; freshening technology; coagulation